(untitled) (Journal of the College of Basic Education, 2022)
Objectives : to assess the level of depression among cancer patients and the chemotherapy side effects and to find out the significant difference between depression level regarding these side effects. Methodology : A descriptive analytical study was conducted on a purposive sample of 50 cancer patients from both sexes who were admitted to Radiation and Neuclur Medicine Hospital in Baghdad for the purpose of giving chemotherapy for the period from April 4th to June 20 th , 2008. A structured interview using the Self Care Diary (SCD) of Nail et al (1991) and Hospital Anxiety and Depression Scale (HADS) was implemented for data collection.